Achievement of the performance Community Health Center Sleman Regency Yogyakarta during the Covid-19 pandemic in 2020 - Tri Hapsari listyaningrum; Heri Puspito (International Journal of Health Science and Technology, 2022)
Health center performance measurement can be measured in a balanced scorecard based on financial perspective, customer perspective, internal business process perspective, learning, and growth perspective. The qualitative study were used in this research will describe the evaluation of the implementation of Primary Health Care management. The four informants used in this study include the head of Primary Health Care, the head of Individual Health efforts, the head of Public Health efforts, and the administration and management, coordinator. Data were analyzed using thematic analysis. The financial perspective performs budget planning according to program achievements. There is an adjustment or shift in the budget in the Expenditure Budget that is diverted for the covid-19 program. From the customer's perspective, the results showed that there was sterilization of facilities, cross-sectoral coordination, and good communication. Patient visits during the COVID-19 pandemic were decreased. The internal business process perspective has innovated with online services, changing service mechanisms, providing additional tasks, and utilizing social media to disseminate information and health education to the public. Several Community Health Efforts activities have been stopped because they have the potential to trigger a wider spread of COVID-19 transmission. Learning and growth perspectives show involve various sectors to support the covid-19 pandemic program, one of which is empowerment by training youth groups for mass vaccination. The business process of one of the Primary Health Care in Sleman Regency runs optimally with various innovations.